Hypnotic communication for periprocedural analgesia during transcatheter ablation of atrial fibrillation. (September 2019) - Scaglione, M.; Battaglia, A.; Di Donna, P.; Peyracchia, M.; Bolzan, B.; Mazzucchi, P.; Muro, M.; Caponi, D.
Abstract: Introduction: Hypnosis is a therapeutic strategy for pain control. We aimed at investigating the use of this technique in a large population undergoing atrial fibrillation (AF) ablation. Methods: 70 consecutive AF patients referred for transcatheter ablation, underwent hypnotic communication for periprocedural analgesia (Group A), were compared with 70 patients undergoing conventional analgesia (Group B). Procedural data, anxiety, perceived pain, perceived procedural duration and the dosages of administered analgesic drugs were compared using validated score scales. Results: Hypnotic communication (Group A) resulted in a significant procedural-related anxiety reduction (Pre procedural 4.7 ± 2.9 Vs Intra Procedural 0.8 ± 1.2, P < 0.001) and perceived procedural duration (Real length 108 ± 33 min Vs Perceived Length 77 ± 39 min, P < 0.001). Group A patients reported a painless procedure in 78% (Pain scale ≤2). Regarding analgesic drug, Group A used only Fentanyl and Paracetamol. The Fentanyl dosage was similar in Group A and B (mean 0.142 Vs 0.146 mg, P = 0.65) while higher Paracetamol dosage was reported in Group A (mean 853 Vs 337 mg, P < 0.001). Group B also used Midazolam (mean 1.8 mg), Propofol (mean 43.8 mg) and narcosis was required in 2 patients. Total radiofrequency (RF) delivered time did not differ between the two groups (mean 28.9 Vs 27.6 min, P = 0.623) as well as mean RF power (mean 35.3 Vs 35.5 W, P = 0.424). No complications occurred. Conclusion: Hypnotic communication during AF ablation was related to a significant reduction of intra-procedural anxiety, perceived pain, procedural analgesic drugs dosage and perceived procedural duration without affecting total RF delivered time and procedural safety.